2004
DOI: 10.1039/b311887h
|View full text |Cite
|
Sign up to set email alerts
|

Bulk synthesis of a-SixNyH and a-SixOy straight and coiled nanowiresElectronic supplementary information (ESI) available: Movies taken using a microscope. File RI19, shows a white fringe (Becke Line), which surrounds the particle, shift into the particle when the lens is moved farther away from focus. This indicates that the RI of the particle is greater than the surrounding calibration solution (RI = 1.9). Files RI21 and RI23 show the Becke line moving from the particle into the surrounding indicating tha

Abstract: We report the bulk synthesis of hydrogenated, amorphous Si x N y and Si x O y nanowires using pools of molten gallium as the solvent medium and microwave plasma consisting of silane in nitrogen and silane in oxygen respectively. High densities of multiple nanowires nucleated and grew from molten gallium pools. The resulting nanowires were tens of nanometers in diameter and tens of microns long. Electron energy loss spectroscopy (EELS) and Fourier transform infra-red (FTIR) spectroscopy showed that the silicon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 17 publications
(23 reference statements)
2
9
0
Order By: Relevance
“…Earlier, we showed that Si nanowire growth using low-melting metal droplets is not limited by the cluster size and occurs at a high density from a single droplet . Later, this concept has been used for demonstrating the synthesis of several materials systems such as Si, Bi, amorphous SiO 2 , and Si x N y H nanowires . In particular, the direct synthesis of nanowires of compounds of low-melting metals such as Group III-nitrides, sulfides, oxides, and so forth under metal-rich conditions fall under this concept as well.…”
Section: Introductionmentioning
confidence: 97%
“…Earlier, we showed that Si nanowire growth using low-melting metal droplets is not limited by the cluster size and occurs at a high density from a single droplet . Later, this concept has been used for demonstrating the synthesis of several materials systems such as Si, Bi, amorphous SiO 2 , and Si x N y H nanowires . In particular, the direct synthesis of nanowires of compounds of low-melting metals such as Group III-nitrides, sulfides, oxides, and so forth under metal-rich conditions fall under this concept as well.…”
Section: Introductionmentioning
confidence: 97%
“…A rich variety of 1D Si or SiO x nanowires have been prepared on the 2D surfaces, like Si wafer and quartz substrates, onto which metal catalysts were deposited by thermal evaporator or sputter. The subsequent thermal annealing process leads to the formation of a metal nanocluster due to an effect of surface tension. , With these approaches, it is not easy to control the size and spatial location of the metal catalyst and it cannot be extended to 3D surfaces, like bulk Si powder. In this study, we employed block copolymer micelles to make uniform-sized Pt nanoparticles.…”
mentioning
confidence: 99%
“…[1][2][3][4] By reducing the sizes of one-and twodimensional nanostructures, unusual transport, structural, and optical properties have been demonstrated. These properties are largely due to the size-dependent quantum confinement effects and additional surface electron states.…”
mentioning
confidence: 99%